Pulmonary epithelioid hemangioendothelioma accompanied by bilateral multiple calcified nodules in lung - Lirong Chen; Jinghong Xu (BMC, 2011)
Abstract Pulmonary epithelioid hemangioendothelioma (PEH) is a rare vascular tumor. It can present either as one solitary nodule or bilateral multiple nodules, usually without calcification. We describe here an unusual case of PEH in a 42-year-old female with a 6.0 cm dominant mass along with bilateral multiple calcified small nodules measuring 0.2-1.0 cm in diameter with a 25-year plus followup history. Overall histologic findings of the solitary tumor accorded with conventional PEH. While multiple calcified small nodules were composed predominantly of intra-alveolar homogeneously eosinophilic matrix, and only a few bland small cells were embedded in it. This lesion has never been reported in the literature. After comprehensive analysis of morphology, radiography, histochemistry, immunohistochemistry and differential diagnoses, PEH presenting multiple calcified small nodules was confirmed.